Perilaku Penggunaan E-Wallet Di Coffe Shop Terhadap Keputusan Penggunaan - Rischa Heni Astriyanita; Ginanjar Rahmawan (JISAMAR (Journal of Information System, Applied, Management, Accounting and Research), 2022)
The development of digital technology is currently changing the behavior of people who used to transact with cash now into non-cash transactions using digital payments through applications available on smartphones. The purpose of this research was to explore the influence of easy to pay, cashless society, security and promotion attraction on the decision to use E-Wallet in Coffe Shop. The technique used in this research is a quantitative approach. The population in this research is the community that uses E-Wallet as a transaction tool. The sampling technique used in the study is non probability sampling with a sample number of 97 people. Sources are consumers in coffe shop who use E-Wallet with the criteria of using more than 2 times. The data used is primary data by spreading questionnaires online. The analysis method used is multiple linear regression with the testing of data instrument reliability and validity, testing of classical assumptions and testing hypotheses t and f using SPSS programs. According to the results of the study, it was obtained that easy to pay and security affect positively but not significantly while cashless society and promotion attraction affect significantly and positively to the decision to use E-Wallet in Coffe Shop. Based on the results of research on the behavior of E-Wallet use in Coffe Shop towards usage decisions obtained conformity value between independent variables to dependent variables amounting to 65.1%.